METHODS OF TEACHING THE CONCEPT OF NUMERICAL EXPRESSION IN PRIMARY GRADES - Roʻzimurodova Rayhona (Bright Mind Publishing, 2025)
This article discusses the methodology of teaching the concept of numerical expressions in elementary school mathematics. It highlights the content of numerical expressions, their analysis, and the development of skills in performing operations with simple and complex numerical expressions. The study explores methodological approaches that contribute to the development of students' mathematical thinking, logical reasoning, and independent working skills. At the end of the article, practical recommendations are provided for elementary school teachers to help enhance the effectiveness of the teaching process.
Keywords: Numerical expression, primary grade, mathematics education, methodology, educational process, arithmetic operations, logical thinking, mathematical thinking, independent thinking